Corrosion-resistant copper-based amorphous alloy and preparation method thereof

By adopting the preparation method of corrosion-resistant copper-based amorphous alloy, the problem of insufficient corrosion resistance of metal materials in the prior art under harsh environments is solved, and excellent corrosion resistance in seawater, strong acids and alkalis are achieved, and the preparation cost is reduced.

CN119710496APending Publication Date: 2025-03-28JIANGSU UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411952359.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when facing harsh environments such as seawater, strong acids and alkalis, the corrosion resistance of metal materials is insufficient, resulting in a shortening of the service life of the equipment, and the preparation process is complex and the cost is high.

Method used

A corrosion-resistant copper-based amorphous alloy with a chemical composition of Cux1Zrx2Alx3Nbx4Tax5 was used, and it was prepared by repeated smelting under vacuum or inert gas protection and single-roll quenching method to obtain an amorphous alloy strip with excellent corrosion resistance.

Benefits of technology

This copper-based amorphous alloy exhibits excellent corrosion resistance in simulated seawater and strong acid and alkali solutions, and is simple in preparation, low in cost, and is suitable for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710496A_ABST
    Figure CN119710496A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant copper-based amorphous alloy and a preparation method thereof, the element composition of the amorphous alloy is Cu, Zr, Al, Nb and Ta, the atomic percentage content of each element is Cux1Zrx2Alx3Nbx4Tax5, 40 < = x1 < = 46.5, 40 < = x2 < = 46.5, 4 < = x3 < = 6, 2 < = x4 < = 4, 2 < = x5 < = 4, and x1 + x2 + x3 + x4 + x5 = 100. Preferably, the atomic percent content of each element is 46.5% of Cu, 44.5% of Zr, 5% of Al, 2% of Nb and 2% of Ta, each performance of the obtained amorphous alloy is well improved, and the amorphous alloy has better thermal stability and excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a corrosion-resistant copper-based amorphous alloy and a preparation method thereof, belonging to the technical field of amorphous alloy materials. Background Art

[0002] Compared with crystalline alloy materials, amorphous alloys have the structural characteristics of long-range disorder and short-range order, and exhibit excellent mechanical, physical and chemical properties. Amorphous alloys do not have defects such as vacancies, dislocations and grain boundaries in the structure of crystalline materials, and it is difficult for ions in the corrosive liquid to enter their interior, showing excellent corrosion resistance. These excellent properties of amorphous alloys make them have great application potential in the fields of marine industry, chemical industry, national defense and military, biomedicine, information storage and new energy.

[0003] Corrosion damage is a common failure mode of metal materials during service, which will cause significant losses and potential harm to the national economy, production and life. At present, there are still many challenges in the field of material corrosion protection, such as the pitting behavior of metals in halides, the damage of seawater and marine microorganisms to marine equipment in the face of marine environments, which will greatly reduce the service life of equipment, and the corrosion of strong acids and alkalis on metals in the chemical industry. Therefore, it is necessary to continuously develop new high-corrosion-resistant materials to meet the harsh service environments such as seawater, strong acids and alkalis.

[0004] Chinese patent literature discloses "a method for improving the ability of zirconium-based amorphous glass to form and corrosion and wear resistance" (publication number: CN116855791A), which reduces its self-corrosion potential by adding trace amounts of rare earth elements. Most of the system elements to which rare earth elements are added have more than five components, and the components are relatively complex. The addition of rare earth elements will not only increase the smelting cost, but also increase the number of components of amorphous alloys and increase the difficulty of preparation. Chinese patent literature "a method for improving the corrosion performance of bulk amorphous alloys by ion implantation" (publication number: CN101021004A) improves the corrosion resistance of amorphous alloys by injecting passivating elements on the surface of amorphous alloys. Although this method does not change the glass-forming ability of amorphous alloys, it has a complex process and high cost.

[0005] In summary, providing an amorphous alloy with simple preparation process, simple composition, low cost and excellent corrosion resistance is of great significance for engineering applications. Summary of the invention

[0006] The object of the present invention is to provide a corrosion-resistant copper-based amorphous alloy and a preparation method thereof. The amorphous alloy has good glass-forming ability, a simple preparation method, and excellent corrosion resistance.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A corrosion-resistant copper-based amorphous alloy, the chemical composition of which is Cu in atomic percentage x1 Zr x2 Al x3 Nb x4 Ta x5 , where 40≤x1≤46.5, 40≤x2≤46.5, 4≤x3≤6, 2≤x4≤4, 2≤x5≤4, and x1+x2+x3+x4+x5=100.

[0009] Preferably, the chemical composition of the amorphous alloy is Cu in atomic percentage. 46.5 Zr 44.5 Al5Nb2Ta2, under this composition, the various properties of the amorphous alloy are greatly improved, with better thermal stability and excellent corrosion resistance.

[0010] The preparation method of any of the above-mentioned corrosion-resistant copper-based amorphous alloys is to repeatedly melt the proportioned metal raw materials (the purity of metal Cu, metal Zr, metal Al, metal Nb and metal Ta is ≥99.9wt%) under vacuum and inert gas protection to obtain an alloy ingot; then melt the alloy ingot under inert gas protection, and cool it by a single-roll quenching method to obtain an amorphous alloy strip.

[0011] Preferably, the vacuum degree is ≤5×10 -3 Pa.

[0012] Preferably, the inert gas is argon.

[0013] Preferably, the smelting condition is: 1500-1650°C.

[0014] Preferably, the smelting times are ≥ 6, each time for 5 min to 7 min.

[0015] Preferably, the alloy ingot is subjected to a surface grinding step before melting to remove the residual impurity layer (or the oxide layer caused by residual oxygen) on the surface of the alloy ingot.

[0016] Preferably, the single-roller rapid cooling method is performed at a cooling rate of 30-40 m / s.

[0017] Preferably, the amorphous alloy strip has a width of 1-2 mm and a thickness of 30-50 μm.

[0018] The beneficial effects of the present invention are:

[0019] The preparation method is simple and the cost is low. The prepared amorphous alloy has good glass-forming ability and exhibits excellent corrosion resistance in simulated seawater and strong acid and alkali solutions without the need for surface treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD pattern (a) and TEM pattern (b) of the corrosion-resistant copper-based amorphous alloy prepared in Example 1;

[0021] Figure 2 The DSC curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1;

[0022] Figure 3 This is a morphology picture of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 after chemical corrosion in 0.5M H2SO4 solution for 70 days;

[0023] Figure 4 This is a morphology picture of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 after chemical corrosion in 1M NaOH solution for 70 days;

[0024] Figure 5 The potentiodynamic polarization curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in a simulated seawater solution (the inset is the open circuit potential OCP spectrum);

[0025] Figure 6 The potentiodynamic polarization curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in 0.5M H2SO4 solution (the inset is the open circuit potential OCP spectrum);

[0026] Figure 7 This is the potentiodynamic polarization curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in 1M NaOH solution (the inset is the open circuit potential OCP curve). DETAILED DESCRIPTION

[0027] The present invention is further described in detail below according to specific embodiments and drawings. The following examples are only exemplary and do not limit the scope of protection of the present invention. In the following embodiments, the amorphous structure of the amorphous alloy strip is determined by Bruker D8A X-ray diffractometer (XRD), transmission electron microscope (TEM) and differential scanning calorimeter (DSC). The corrosion rate is determined by natural immersion weight loss method at room temperature, and the self-corrosion current density and self-corrosion potential are obtained by electrochemical workstation testing.

[0028] Example 1

[0029] Weigh the raw materials according to the atomic percentage of Cu 46.5%, Zr 44.5%, Al 5%, Nb 2%, and Ta 2%, with a total weight of 30g, of which the metal blocks of Cu, Zr, Al, Nb, and Ta are 11.5168g, 15.8222g, 0.5260g, 0.7239g, and 1.4114g respectively. Put the prepared raw materials into a vacuum arc furnace and the vacuum degree reaches 5×10 -3Pa, with argon as the protective gas, the smelting was repeated at 1550°C for more than 6 times (6 min each time) to obtain a uniformly smelted alloy ingot.

[0030] The smelted alloy ingot is polished to remove the residual impurity layer (or the oxide layer caused by residual oxygen) on the surface, and then the polished alloy ingot is cut into a suitable size and placed in a quartz tube. The quartz tube is placed in an induction coil in a belt-spinning machine, and the alloy ingot in the quartz tube is heated by the induction coil. When the alloy ingot in the quartz tube is observed to be in a molten state, the pressure difference is used to spray the high-temperature melt onto a rapidly rotating water-cooled copper roller to prepare an alloy strip. The width of the alloy strip is 1-2 mm and the thickness is 30-50 μm.

[0031] Figure 1 These are the XRD patterns (a) and TEM patterns (b) of the corrosion-resistant copper-based amorphous alloy prepared in Example 1. The XRD pattern shows that the corrosion-resistant copper-based amorphous alloy has a broadened diffuse diffraction peak (mantou peak) without a sharp crystallization peak, indicating that the copper-based amorphous alloy is an amorphous alloy. The TEM high-resolution image and the corresponding diffraction rings also show that the copper-based amorphous alloy is a fully amorphous structure.

[0032] Figure 2 is the DSC curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1, from which the glass transition temperature T g =694K, crystallization temperature T x =758K, as the temperature rises to the glass transition temperature (T g ), a small endothermic zone appears, and the temperature rises to the crystallization temperature (T x ), an obvious exothermic phenomenon occurred, and the supercooled liquid phase region ΔT = 64K, indicating that the copper-based amorphous alloy has good glass-forming ability.

[0033] Table 1 shows the corrosion rates of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in simulated seawater (3.5wt.% NaCl), 0.5MH2SO4 and 1M NaOH solutions. The results show that the corrosion rates of the copper-based amorphous alloy in acids, bases and salts are relatively small, showing excellent corrosion resistance. The corrosion rate of the amorphous alloy in acid and alkali solutions is much lower than that in simulated seawater, indicating that it has more excellent corrosion resistance in acid and alkali solutions. The corrosion rate of the amorphous alloy was obtained by natural immersion corrosion in simulated seawater, 0.5MH2SO4 and 1MNaOH solutions (natural immersion weight loss method at room temperature).

[0034] Table 1

[0035]

[0036] The specific operation in the simulated seawater solution is as follows: a 40 mm long strip is taken as a natural immersion test sample with a width of 2 mm. The corrosion solution is changed every 2 days. The sample is ultrasonically cleaned before weighing. The initial mass of the sample is 15.754 mg, and the mass after 24 days is 4.82 mg. The mass loss ratio is 69.4%. Pitting corrosion occurs on the surface of the copper-based amorphous alloy prepared in Example 1, and the corrosion rate is 0.296 mm / year.

[0037] The specific operation in 0.5M H2SO4 and 1M NaOH solution is as follows: the strip length for natural immersion is 40mm and the width is 2mm. The etching solution is changed every 2 days. The sample is ultrasonically cleaned before weighing. The corrosion rates of the copper-based amorphous alloy prepared in Example 1 in 0.5M H2SO4 and 1M NaOH solutions are 2.883×10 -4 mm / year and

[0038] 3.853×10 -4 mm / year.

[0039] The surface corrosion morphology of the copper-based amorphous alloy prepared in Example 1 after being immersed in 0.5M H2SO4 and 1M NaOH solutions for 70 days is shown in Figure 2. Figure 3 and Figure 4 . Figure 3 and Figure 4 It shows that after the copper-based amorphous alloy prepared in Example 1 was immersed in 0.5M H2SO4 and 1MNaOH solutions for 70 days, its surface was still flat and smooth without obvious corrosion marks, indicating that the passivation film formed on the surface of the sample was stable and could resist SO4 2- and OH - The corrosion of ions shows that copper-based amorphous alloys have excellent corrosion resistance in strong alkali and strong acid solutions.

[0040] Figure 5 The potentiodynamic polarization curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in simulated seawater solution is shown in the figure (the inset is the open circuit potential OCP spectrum). Before testing the potentiodynamic polarization curve, the open circuit potential is tested for 7200s, and the potentiodynamic polarization curve is tested again after the potential is stabilized. The self-corrosion potential E of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in simulated seawater is corr is -399mV, self-corrosion current density I corr is 4.4×10 -6 A / cm 2 , see Table 2.

[0041] Figure 6The potentiodynamic polarization curve of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in 0.5M H2SO4 solution (the inset is the open circuit potential OCP spectrum). The open circuit potential is tested for 7200s, and then the potentiodynamic polarization curve is tested after the potential stabilizes. The self-corrosion potential E of the corrosion-resistant copper-based amorphous alloy in 0.5M H2SO4 solution is shown in Figure 1. corr is -53mV, self-corrosion current density I corr is 3.0×10 -8 A / cm 2 , see Table 2.

[0042] Figure 7 The potentiodynamic polarization curve spectrum of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in 1M NaOH solution (the inset is the open circuit potential OCP spectrum). Before testing the potentiodynamic polarization curve, the open circuit potential was tested for 7200s, and the potentiodynamic polarization curve was tested again after the potential was stabilized. The self-corrosion potential E of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in 1M NaOH solution corr is -316mV, self-corrosion current density I corr 9.0×10 -8 A / cm 2 , see Table 2.

[0043] Table 2

[0044]

[0045] Table 2 is a comparison of the electrochemical corrosion performance of metal materials reported in the literature and the present invention in strong acid and alkali and simulated seawater solutions. The self-corrosion current density of a material can characterize the corrosion resistance of the material. The smaller the self-corrosion current density of the material, the better the corrosion resistance of the material. The self-corrosion current density of the corrosion-resistant copper-based amorphous alloy prepared in Example 1 in a simulated seawater solution is basically equivalent to that of stainless steel, which is 0.407 times that of the CuZr-based amorphous alloy; the self-corrosion current density in H2SO4 solution is 0.026 times that of 316L stainless steel; the self-corrosion current density in NaOH solution is 0.191 times that of the zirconium-based amorphous alloy and 0.047 times that of the iron-based amorphous alloy.

[0046] In summary, the copper-based amorphous alloy provided in the present application has excellent corrosion resistance in acid, alkali and salt solutions, especially in strong acid and alkali solutions, and its corrosion resistance is better than that of traditional alloy materials.

[0047] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the protection scope of the patent of the present invention.

Claims

1. A corrosion-resistant copper-based amorphous alloy, characterized in that: The chemical composition of the amorphous alloy is calculated by atomic percentage: Cu x1 Zr x2 Al x3 Nb x4 Ta x5 , where 40≤x1≤46.5, 40≤x2≤46.5, 4≤x3≤6, 2≤x4≤4, 2≤x5≤4, and x1+ x2+x3+x4+x5=100.

2. The corrosion-resistant copper-based amorphous alloy according to claim 1, characterized in that: The chemical composition of the amorphous alloy is Cu in atomic percentage. 46.5 Zr 44.5 Al5Nb2Ta2.

3. The method for preparing the corrosion-resistant copper-based amorphous alloy according to any one of claims 1 to 2, characterized in that: The method comprises smelting the proportioned metal raw materials under vacuum and inert gas protection to obtain alloy ingots; then melting the alloy ingot under inert gas protection, and cooling the alloy ingot by single-roll rapid cooling to obtain amorphous alloy strips.

4. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: Vacuum degree ≤5×10 -3 Pa.

5. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: The inert gas is argon.

6. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: The smelting conditions are: 1400-1650℃。 7. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 6, characterized in that: Melting times ≥ 6, 5min-7min each time.

8. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: The alloy ingot was also subjected to a surface grinding step before melting.

9. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: The conditions of the single-roll rapid cooling method are: cooling speed 30-40m / s.

10. The method for preparing the corrosion-resistant copper-based amorphous alloy according to claim 3, characterized in that: The width of the amorphous alloy strip is 1-2 mm and the thickness is 30-50 μm.

Citation Information

Patent Citations

  • Ion implantation process to raise anticorrosion performance of lumpy amorphous alloy

    CN101021004A

  • Method for improving zirconium-based amorphous forming ability and corrosion and wear resistance

    CN116855791A